A Custom Probe Station for Microstrip Detector Quality Assurance of the CBM Experiment. (August 2016) - Panasenko, I.; Lavrik, E.; Lymanets, A.; Schmidt, H. R.
Abstract: The double-sided silicon microstrip sensors with 58 µm pitch are the main building blocks of the Silicon Tracking System (STS) — the central detector of the Compressed Baryonic Matter (CBM) Experiment. The STS will employ about 1200 such sensors arranged on eight traking stations. Electrical characterization of the sensors is necessary to ensure their compliance with the specifications. For this purpuse a custom probe station is being developed at Tuebingen University. One of the main requirements is a high accuracy and a repeatability better than 1 µm to allow an automatic, succesive positioning on all 1024 pads of a sensor, as well as a positioning range in accordance with the size of STS sensors. The probe station is controlled via dedicated software developed at Tuebingen University. It allows to inspect the required 10% of the sensors on the series production stage with characterization time 4-5 hours per one double-sided sensor. The construction of the probe station and first measurements are discussed in this paper.